Bispecific Antibodies for Targeted Delivery of Dendritic Polyglycerol (dPG) Prodrug Conjugates - Sheikhi Mehrabadi, Fatemeh; Adelmann, Juliane; Gupta, Shilpi; Wedepohl, Stefanie; Calderón, Marcelo; Brinkmann, Ulrich; Haag, Rainer (Current Cancer Drug Targets, 2016)
One approach to further improve the therapeutic efficacy of nanoparticles is employment of active targeting strategies. Bispecific antibodies (bsAbs) that bind to both tumor specific antigens on the cell surface and to haptens such as digoxigenin (Dig) can direct digoxigeninylated payloads to tumor cells. In this study, we investigate the potential of dendritic polyglycerol (dPG) conjugates, which consist of a doxorubicin (DOX) prodrug, Dig moiety, and a poly (ethylene glycol) (PEG) shell, in combination with bsAb, as a novel approach for targeted prodrug delivery. We could show successful binding of the bsAbs to dPGDigMal-DOX-PEG conjugates, as well as binding of these complexes to the cell surface of Lewis Y (LeY) expressing MCF-7 cells. Using flow cytometry, we could show the preferential binding of the targeting complex over the complex of control conjugate lacking Dig moieties. At concentrations that are usually applied for drug delivery, antibodycomplexed nanoparticles (independent of antibody specificity) released cytotoxic compounds into cells to the same degree as unmodified nanoparticles. This indicates that antibody-attachment does not interfere with the inherent cell binding and drug delivery properties of nanoparticles. At low doxorubicin concentrations and short incubation times, however, we were able to see a slightly increased target specific cytotoxicity in vitro which is mediated by complexation of the digoxigeninylated NP with the Dig-binding moiety of a bsAb that in turns direct the complexed bsAb to target cells. This study demonstrates the potential of digoxigeninylated dPG prodrug conjugates in combination with bsAbs as a new platform for targeted prodrug delivery into cancerous tissues. However the nanoparticle design needs to be further optimized for significant targeted delivery.
Keywords: doxorubicin